Tobacco Cessation and Substance Abuse Treatment in Women's Healthcare A Clinical Guide - Calhoun, Byron C.; Lewis, Tammi (Springer International Publishing : Imprint: Springer, 2016)
This book is a comprehensive guide to the screening, management, and treatment of female patients with addictions. There are a range of clinical issues specific to women with substance use disorders and substance abuse during pregnancy is known to have deleterious effects on neonates. This book focuses on the effective care of the addicted patient and discusses novel outpatient therapy, therapeutic substitution, abstinence therapy, and the importance of counseling in the delivery of care. Topics include the physiology of nicotine, opiates, EtOH, and other substances of abuse; the role of receptors and neurotransmitters in addiction; the effects of tobacco and substance abuse on women' s health; and tobacco cessation methods. Featuring practical approaches to gender-responsive treatment, Tobacco Cessation and Substance Abuse in Women's Healthcare is a valuable resource for obstetricians, gynecologists, family medicine practitioners, and residents hoping to expand their knowledge of tobacco cessation and substance abuse in women's health. .